ASTM E928-03, Standard Test Method for Determination of Purity by Differential Scanning Calorimetry. - ASTM International (West Conshohocken (Pa.) : ASTM International, 2003)
1.1 This method describes the determination of purity of materials greater than 98.5 mole percent purity using differential scanning calorimetry and the van't Hoff equation. 1.2 This test method is applicable to thermally stable compounds with well-defined melting temperatures. 1.3 Determination of purity by this test method is only applicable when the impurity dissolves in the melt and is insoluble in the crystal. 1.4 Computer- or electronic-based instruments, techniques, or data treatments equivalent to this test method may also be used. Note 1-Since all data treatments are not equivalent, it is the responsibility of the user to verify equivalency prior to use. 1.5 SI values are the standard.
Keywords: Normen